Prevalencia de Neospora caninum en bovinos localizados en fincas del cantón Chone provincia de Manabí - Mora Alzate, Emmanuel (2024)
The objective of this research was to determine the prevalence of Neospora caninum in crossbred cows located on farms in Chone canton, Manabí province. A total of 184 samples were analyzed, collected from the parishes Eloy Alfaro, Ricaurte, and Convento. The data obtained were subjected to descriptive statistical analysis to evaluate the distribution of the infection in the different localities and provide a detailed understanding of its incidence in the region. The prevalence of Neospora caninum in Eloy Alfaro parish was 11.41%, Ricaurte 4.89%, and Convento 2.71% in Chone canton, for a total of 19.01% across the investigated parishes. Mapping allowed for the identification of areas with the highest incidence, visualizing the spread of diseases, and determining the most vulnerable zones. The main risk factors identified were: failure to apply quarantine, inadequate waste management, and the absence of health plans. The prevalence of Neospora caninum was 19.01%, with the highest incidence in the Eloy Alfaro parish of Chone canton.